Validity test using LISREL on the academic anxiety instrument using the Confirmatory Factor Analysis Method - Dela Putri, Zhi Zhi Oktaviani; Herdi, Herdi (Universitas Islam Negeri Raden Intan Lampung, 2023)
Academic anxiety in students is a concern for education. The problem that arises is the high level of academic anxiety among students, which is caused by several factors. Ottens believes that academic anxiety arises when a person experiences disturbances in thought patterns, behavior, and physiological responses due to feelings of excessive worry about academic performance. It consists of 4 dimensions, namely anxiety that results in mental activity (patterns of anxiety-engendering mental activity), forms of interest that show the wrong direction (misdirected attention), physical distress (physiological distress), and inappropriate actions (inappropriate behaviors). It will reduce students’ learning motivation, so they tend to look for alternative ways to overcome their academic anxiety, for example, in a negative way, namely making cheat sheets during exams, which will reduce their academic integrity. Therefore, researchers will measure students’ academic anxiety levels at SMAN 75. The data in this study was obtained from 254 students at SMAN 75. Test the validity of this instrument using LISREL and Amos software with the confirmatory factor analysis (CFA) program. The results stated that of 27 items in this instrument, three were irrelevant or invalid. So, if you drop it, you are left with 24 items that are only one aspect.